Skateboard-associated injuries: Participation-based estimates and injury characteristics - Kyle, S. B.; Nance, M. L.; Rutherford Jr, G. W.; Winston, F. W. (The Journal of Trauma: Injury, Infection, and Acute Care Surgery, 2002)
Background: Skateboarding is a popular recreational activity but has attendant associated risks. To place this risk in perspective, participation-based rates of injury were determined and compared with those of other selected sports. Skateboard-associated injuries were evaluated over time to determine participation-based trends in injury prevalence.